The Influence of Learning Models Think Talk Write to Ability to Analyze the Structure and Language of Expository Texts for students of class X of SMA Negeri 1 Panyabungan - Shoufi Nisma Dewi (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
The purpose of this study was to determine the effect of the Think Talk Write learning model on the ability to analyze the structure and language of expository texts in class X students of SMA Negeri 1 Panyabungan. This research method uses a descriptive method with a quantitative approach. The population of this study was all class X students of SMA Negeri 1 Panyabungan totaling 182 students. The sampling technique was carried out randomly, so class X 4 was selected with 36 students consisting of 15 male students and 21 female students. The data collection technique used a test in the form of 10 multiple choice questions and 1 fill-in-the-blank question. Based on the data analysis, the results of the use of the Learning Model were obtained. Think Talk Write with an average value of 84.44, while the students' ability to analyze the structure and language of expository texts obtained an average value of 79.58. The results of the